SISTEM PERANCANGAN ALAT PENDETEKSI TINGKAT KEMATANGAN BUAH TOMAT MENGGUNAKAN SENSOR WARNA BERBASIS ARDUINO - Rifki Pebri Ardiyan; Ari Syaripudin (CV. Multi Kreasi Media, 2023)
The development of science and technology has made the quality of human life increasingly developed, the agricultural and plantation product processing industry has also developed rapidly. One of the stages in the processing of agricultural and plantation products is the selection of products based on their quality, for example the maturity level of tomatoes. In the process of checking tomatoes, it is still done manually and is done based on the visible color so that it can take a long time to choose. To solve the problem, it is necessary to do research by designing tools that can help traders work in the process of detecting the ripeness level of tomatoes. The tool is designed to use a sensor type TCS3200 as a tool to determine the color composition of tomatoes and then processed by Arduino as a DC motor controller and a servo motor to sort fruit based on red, green. In this method using the method of preliminary studies, heritage studies, preparation, tool design, tool manufacture, tool testing and analysis, conclusions. The results of the study carried out 10 × testing, there were 7 × successful and 3 × errors. From these tests it can be concluded that the accuracy rate of the tool is 70%.